Advokasi Kebijakan Pemerintah Daerah dalam Urusan Pelindungan Mata Air Demi Kelangsungan Hidup Masyarakat Kabupaten Bandung: Advocacy for Local Government Policies on Spring Water Protection to Ensure the Livelihood of the People of Bandung Regency - Karina Puji Fauziah (SIYASI: Jurnal Trias Politica, 2024)
Water is a vital resource for human life and ecosystems, yet its existence is increasingly threatened by population growth, industrialization, and environmental degradation. Bandung Regency has abundant spring water potential; however, only about 19.48% of its residents obtain clean water access from the government, while the rest depend on private providers and community initiatives. This condition indicates weak management and protection of spring water at the regional level. This study aims to analyze the urgency of spring water protection in Bandung Regency and to examine policy advocacy efforts through the drafting of a Regional Regulation (Raperda) on Spring Water Protection. The research employs literature review, policy analysis, and documentation of the process from the preparation of the academic manuscript to the discussion of the Raperda. The findings show that the local government and the Regional House of Representatives (DPRD) have carried out a series of stages, including problem identification, literature review, comparative studies, focus group discussions (FGD), regulatory review, and public hearings involving academics, communities, and stakeholders. The Raperda outlines the scope of regulation covering conservation, maintenance, restoration, utilization, licensing, and community participation in spring water protection. In conclusion, protecting spring water through regional policies is crucial to ensuring sustainable clean water supply, preserving ecosystems, and achieving equitable welfare for the people of Bandung Regency.